The Effect of Work Motivation and Discipline on Employee Performance in Associations Indonesian Hypertension Doctor (PERHI) Jakarta - Muratin Muratin (International Journal of Education, Information Technology, and Others, 2022)
This study aims to determine whether motivation and work discipline affect the performance of the employees of the Indonesian Hypertension Doctors Association (PERHI) Jakarta. The research method used is descriptive quantitative with a questionnaire as a data source. The population in this study were 56 employees of the Indonesian Hypertension Doctors Association (PERHI) in Jakarta. The sample in this study were 56 people as respondents. The analytical tool in this study is multiple linear regression. The next stage is the questionnaire data was analyzed with the SPSS computer program tool. The results showed that there was a positive and significant influence between motivation (X1) and work discipline (X2) on employee performance (Y), this was proven by a significance level of 0.000< 0.05 then Ho is rejected. and Ha accepted